The Influence of Administrative Procedure of Online Registration of Job Seekers to The Effectiveness of a Yellow Card on The Department of Employment Cianjur District - Ira Septira Aripin; Tias Safira Handayani; Wilma Zuarko Adji (Department of Public Administration, 2021)
Department of employment Cianjur District is a government agency that provides yellow card making service using online administration procedures, where the public required to be able mastering technology that are always changing. The research aimed to find effective yellow card making online, improving service quality is the main goal in the policy. The writer does the research used quantitative and descriptive. The research conducted against yellow card makers and employees department of employment Cianjur districk, The technique data collection used with observation, dokumentation, written interview also literature review which has close relationship from the subject matter, the data is processed using descriptive analysis. From this research the results is that yellow card making online 99% can be effective time and cost also makes it easier for the public making yellow card.